Vegetative growth of of Amorphophallus titanum (Becc.) Becc. at Cibodas Botanic Garden - R. SHOLIHIN; R. SUBEKTI PURWANTORO (Society for Indonesian Biodiversity, 2005)
A study on the growth of vegetative stadium of Amorphophallus titanum (Becc.) Becc. has been carried out in Cibodas Botanic Garden. Two bulbs are planted as collection plants since June second 2000. The big one, before dormant was in generative stadium and the other bulb is small one, before dormant was in vegetative stadium. The result of this study indicate that the growth of the big bulb longer than small one. The effect of different stadium before dormant cause the early growth of big bulb is longer than the small one.@2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: Amorphophallus titanum, growth.